Evaluation of Corporate University Program in the Field of Training and Competence Development State Civil Apparatus - Nisrina Nur Alfi Laili; Sri Wulandari (Pusat Publikasi Nusantara, 2026)
This study aims to evaluate the effectiveness of the Corporate University (Corpu) program in training and developing the competencies of State Civil Apparatus (ASN) within the Cirebon Regency Personnel Development and Human Resources Agency (BKPSDM). The evaluation theory used by William Dunn: Effectiveness, efficiency, adequacy, responsiveness, equity, and accuracy. The approach through qualitative phenomenology to explore the experiences and perspectives of both program managers and training participants. Data were collected through interviews, observations, and documentation, then analyzed using the interactive model of Miles and Huberman. The results of the study indicate that the Corpu program overall runs quite well, the Corpu program has provided benefits in improving ASN understanding of job responsibilities, as well as encouraging experiential learning and the use of technology. However, the implementation of the Corpu program has not been fully optimal because it still faces limitations in digital literacy, network infrastructure constraints, budget limitations and unequal access to training. This study emphasizes the importance of continuous evaluation of ASN competency development policies to strengthen the effectiveness and sustainability of Corpu at the local government level.